2015
DOI: 10.1039/c4cs00329b
|View full text |Cite|
|
Sign up to set email alerts
|

Structure, function, self-assembly, and applications of bottlebrush copolymers

Abstract: Bottlebrush polymers are a type of branched or graft polymer with polymeric side-chains attached to a linear backbone, and the unusual architecture of bottlebrushes provides a number of unique and potentially useful properties. These include a high entanglement molecular weight, enabling rapid self-assembly of bottlebrush block copolymers into large domain structures, the self-assembly of bottlebrush block copolymer micelles in a selective solvent even at very low dilutions, and the functionalization of bottle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
561
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(580 citation statements)
references
References 143 publications
4
561
1
1
Order By: Relevance
“…66 The unusual architecture of CPBs gives them some unique properties such as large dimensions of macromolecules, a low entanglement extent, and a lower critical micelle concentration (CMC). 67 It has been shown that CPBs with poly(L-lysine) side chains and sodium dodecylsulfate (SDS) can form complexes with intriguing structures. 80 An increasing amount of SDS initiates the complex transformation to a helical conformation with a local ÎČ-sheet structure on the side chains, followed by a spherically collapsed structure formation.…”
Section: Assembly Of Cylindrical Polyelectrolyte Brushesmentioning
confidence: 99%
“…66 The unusual architecture of CPBs gives them some unique properties such as large dimensions of macromolecules, a low entanglement extent, and a lower critical micelle concentration (CMC). 67 It has been shown that CPBs with poly(L-lysine) side chains and sodium dodecylsulfate (SDS) can form complexes with intriguing structures. 80 An increasing amount of SDS initiates the complex transformation to a helical conformation with a local ÎČ-sheet structure on the side chains, followed by a spherically collapsed structure formation.…”
Section: Assembly Of Cylindrical Polyelectrolyte Brushesmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] However, bottlebrush block polymers display much larger scaling exponents (ïĄ = 0.8-0.9), [21][22][23][24] consistent with extended backbone conformations. Steric repulsion between the densely grafted side chains imparts a certain bending rigidity to the backbone, which can be modeled as a wormlike chain.…”
mentioning
confidence: 99%
“…8 Congestion imparted by the repeat units enforces the polymer main-chain elongation with a low potential for chain entanglement. 9 Molecular brush copolymers can be synthesized by graftingfrom, grafting-to, and grafting-through strategies. 10 Using ruthenium mediated ring-opening metathesis polymerization (ROMP), we have been interested in the grafting-through approach, directly polymerizing norbornene-functionalized macromonomers, ensuring that every repeat unit consists of a polymeric repeat unit, to well-defined brush BCPs.…”
Section: Introductionmentioning
confidence: 99%